2021
DOI: 10.5304/jafscd.2021.104.004
|View full text |Cite
|
Sign up to set email alerts
|

Market challenges for local specialty crop producers during the early phase of COVID-19 in North Carolina

Abstract: In March of 2020, as the number of COVID-19 cases increased in North Carolina (NC), the state encouraged people to stay at home; this included closing restaurants and canceling large events, as well as reducing the number of people gathering. The economic and health crises created by COVID-19 forced specialty crop producers who sell to local markets, such as restaurants and institutions, to pivot their marketing plans as the growing season began to ramp up. This article reports the responses to the first in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In general, farmers were able to make the decision to grow different and diverse crops, problem-solve in ways they saw fit, and, importantly, shift market channels. Market-channel pivots during the pandemic were common among small farms across the U.S. (Dankbar et al, 2021;Lemos & Ackoff, 2020;Local Food Research Center, 2021;White, 2021), and in international studies have been associated with positive outcomes (Benedek et al, 2021;Hsiao et al, 2021;Mastronardi et al, 2021).…”
Section: Adaptive Capabilitymentioning
confidence: 99%
“…In general, farmers were able to make the decision to grow different and diverse crops, problem-solve in ways they saw fit, and, importantly, shift market channels. Market-channel pivots during the pandemic were common among small farms across the U.S. (Dankbar et al, 2021;Lemos & Ackoff, 2020;Local Food Research Center, 2021;White, 2021), and in international studies have been associated with positive outcomes (Benedek et al, 2021;Hsiao et al, 2021;Mastronardi et al, 2021).…”
Section: Adaptive Capabilitymentioning
confidence: 99%
“…Hege et al (2021) describe this as a "perfect storm" (p. 241) where the confluence of many food system impediments forced organizations to innovate quickly. In North Carolina, many specialty-crop producers reported significant damage to their businesses as a result of the pandemic (Dankbar et al, 2021). The lost or reduced capacity of previously established supply chains required producers to rework their operations and oftentimes sell directly to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, many food system stakeholders have had to make immediate pivots or pursue innovations in response to changes in demand (e.g., increases for food pantries, decline in customers for restaurants), public health guidance (e.g., distributing food boxes instead of allowing clients to "shop" through pantries, acquiring masks, and shifting to online communications), and supply-chain disruptions (e.g., finding new sources for restaurants, piloting direct-to-consumer programs) (Dankbar et al, 2021;Hege et al, 2021). At the same time, scholars suggested that the crises evident during the pandemic created an opportunity to rebuild food systems that are more just and sustainable (Blay-Palmer et al, 2021;Cox & Beynon-MacKinnon, 2020;Glaros et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…describe this as a "perfect storm" (p. 241) where the confluence of many food system impediments forced organizations to innovate quickly. In North Carolina, many specialty-crop producers reported significant damage to their businesses as a result of the pandemic (Dankbar et al, 2021). The lost or reduced capacity of previously established supply chains required producers to rework their operations and oftentimes sell directly to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, many food system stakeholders have had to make immediate pivots or pursue innovations in response to changes in demand (e.g., increases for food pantries, decline in customers for restaurants), public health guidance (e.g., distributing food boxes instead of allowing clients to "shop" through pantries, acquiring masks, and shifting to online communications), and supply-chain disruptions (e.g., finding new sources for restaurants, piloting direct-to-consumer programs) (Dankbar et al, 2021;. At the same time, scholars suggested that the crises evident during the pandemic created an opportunity to rebuild food systems that are more just and sustainable (Blay-Palmer et al, 2021;Cox & Beynon-MacKinnon, 2020;Glaros et al, 2021).…”
Section: Introductionmentioning
confidence: 99%